HF-Components for Harsh Environments using Investment Casting with Additive Manufacturing - Panusch, David; Gold, Gerald (WISEE -THE IEEE WIRELESS IN SPACE AND EXTREME ENVIRONMENTS CONFERENCE, 2024)
Recently, investment casting has been proposed for the production of microwave components. This novel manufacturing method combines the advantages of additive manufacturing with a robust all-metal structure. This makes it particularly suitable for aerospace, maritime and other applications where durability, temperature range and stiffness are required. In this talk, casted waveguides with different metal alloys will be compared to their conventional equivalents, i.e. milled split blocks. Through and resonator measurements were performed to determine the effective conductivity, which includes not only the conductivity but also the effect of surface roughness. In addition, the surface profiles of the samples were measured. Future applications could benefit from this fabrication approach with few overall design constraints. However, morphological optimization of the components, e.g. structural reinforcements, is essential for mechanical stability, where the trade-off between weight, electrical performance and stiffness must be considered. This is demonstrated using a corrugated horn antenna array for E-band applications.<br